2021
DOI: 10.1089/heq.2020.0141
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Health Disparities and Socioeconomic Status in Emergent Gastrointestinal Procedures

Abstract: Objectives: There is limited data describing the role of health disparity factors and socioeconomic status (SES) on emergent versus nonemergent gastrointestinal (GI) procedures within pediatrics. We aimed to characterize risk factors and determine the role of SES on emergent versus nonemergent GI care. We hypothesized that patients with lower SES incur higher risk of having emergent procedures performed. Methods: Retrospective chart review was performed between 2012 and 2016, with 2556 patient records reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…demonstrated that Black and underinsured patients had worse outcomes and greater resource utilization in non-variceal UGIB [19]. Disparity in care for vulnerable populations has been shown to be widespread in medicine and prevalent amongst diverse specialties and subspecialties [14,[20][21][22]. These studies have included elderly patients as a group with worse outcomes but have typically associated these outcomes with underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that Black and underinsured patients had worse outcomes and greater resource utilization in non-variceal UGIB [19]. Disparity in care for vulnerable populations has been shown to be widespread in medicine and prevalent amongst diverse specialties and subspecialties [14,[20][21][22]. These studies have included elderly patients as a group with worse outcomes but have typically associated these outcomes with underlying comorbidities.…”
Section: Discussionmentioning
confidence: 99%